A Focused Review on Engineering Application of Multi-Principal Element Alloy - Chen, Yang; Xie, Baobin; Liu, Bin; Cao, Yuankui; Li, Jia; Fang, Qihong; Liaw, Peter K. (Frontiers in Materials, 2022)
Compared with traditional alloys with one principal component up to 40% - 90%, multi-principal-element alloys (MPEAs) were born in the complicated intermingling of traditional and non-traditional physical metallurgy, and brings us a great amount of excellent performances. Here, we would briefly summarize the potential applications in some key areas, which is helpful for latecomers to quickly and comprehensively understand this new alloy system. Especially, the applications of MPEAs in aerospace, industrial equipment, national defense, energy, navigation and so on are discussed roughly. Subsequently, several emerging areas have also been compared. Finally, some suggestions are given for the future development trend.